The Roles of Libraries in Education - Boucher, Julie J.; Lance, Keith Curry; Colorado State Dept. of Education, Denver. State Library and Adult Education Office (New Delhi : Beacon books, 1994)
Three sets of roles that libraries play in education are identified. Each of the roles is explained, accompanied by relevant statistics and examples. In the first place, libraries provide access to education by teaching information skills, by providing leadership and expertise in the use of information and information technologies, and by participating in networks that enhance access to resources outside the school or community. Secondly, libraries help ensure equity in education by: (1) helping children start school ready to learn; (2) addressing the needs of student most at risk; (3) providing access to information and ideas unimpeded by social, cultural, and economic constraints; (4) ensuring free and equal access to information and ideas without geographic constraints; and (5) helping students stay free of drugs and violence, in an environment conducive to learning. A third role is that of impacting academic achievement for individuals and assisting them in lifelong learning, preparing individuals for productive employment, promoting the enjoyment of reading, promoting functional literacy among adults, preparing individuals for responsible citizenship, and equipping the United States to be first in the world in science and mathematics achievement. Specific examples illustrate Colorado libraries that carry out these roles. (SLD)
Includes bibliographical references
Microfiche.
Keywords: Academic Achievement; Access to Education; Access to Information; Educational Environment; Elementary Secondary Education; Equal Education; High Risk Students; Information Technology; Information Utilization; Library Networks; Library Role; Library Services; Public Libraries; School Libraries; School Readiness; Users (Information); Colorado -- Examples; Reports, Descriptive